Factors to be considered in the adoption of the matrix management organisation structure within a state-owned enterprise - Brukwe, Athayanda (Department of Construction Economics and Management, 2022)
The aim of the research was to investigate the factors to be considered in the adoption of the matrix management organization structure within State-Owned Enterprises. It also investigated how the employees understand the project matrix management organization structure and its application, how they observe it to be and whether their misunderstanding of their roles in the structure will have an impact on meeting the project objectives and performance. This research also investigated whether the utilization of the project matrix management organization structure promotes the successful completion of project or whether it delays the project. The problem examined was “the State-Owned enterprise is still experiencing problems meeting project objectives despite implementing the matrix management organization structure which was intended to facilitate the meeting of project objectives within the organization”. The misunderstanding on the roles and functions of personnel within a project environment using the matrix organization structure was also investigated on whether it has an impact on meeting project objectives and performance. The research question for this study was: “What are the factors that hinder or support the State-Owned Enterprise with the adoption of the matrix management organization structure to meet its project objectives?” The research paradigm was interpretivist. The strategy used was empirical, with an inductive approach. The study approach was qualitative with a survey questionnaire and semi-structured interviews as data collection methods and the data analysis was thematic. The following were the key findings of the study: In terms of awareness of the structure, most respondents advised that the organisation is using a project matrix management organisation structure. The enablers that were agreed on are managing complexity, resource efficiency, communication effectiveness and output quality. The barriers that were agreed on were ambiguous authority and dual reporting, decision-making delays, management of cross-functional teams, lack of a matrix guardian and level of conflicts. The indication in terms of cost performance was that the projects had cost implications. Most projects were completed on budget with 51% indicating that the projects had an overspend. 74% indicated that the projects that they have worked on were completed behind schedule. 16% indicated that the projects were completed on time. The perception is that this type of structure, due to the number of the managers that are involved lacks decision making. The lack of decision making is caused by lack of communication and stakeholder engagement. Stakeholder engagement was also an issue that was highlighted as lacking.